Impact of training on cybersecurity awareness / Zuriani Ahmad Zukarnain ... [et al]. - Ahmad Zukarnain, Zuriani; Hashim, Mimi Zazira; Muhammad, Norrini; Mansor, Farah Ahlami; Wan Azib, Wan Nor Hazimah (Universiti Teknologi MARA Cawangan Pahang, 2020)
Studies show that training is a good alternative to deliver cybersecurity knowledge to children. This paper reports on the findings of a study after conducting awareness training programs. The ultimate goal of the program is to help children to understand issues related to cybersecurity and instill the cybersecurity awareness. Children are now discovering computers, smartphones or tablets at an early age. Even though an internet connection of the computers and mobiles devices can be useful for learning as well as enhancing social relations and keeping the young users connected to their parents, it can also be a source of danger and concern for parents. Hence, safer browsing habits need to be nurtured earlier among them. Cybersecurity awareness training was conducted to deliver the content to the targeted group. The objectives of this study are to examine cybersecurity awareness after the participants have gone through the training, to improve a better understanding on cybersecurity awareness and finally to promote safer browsing habits. The cybersecurity awareness is important to develop a good digital citizenship among the young generation. The content of the training includes topics on cybersecurity threats such as pornography, pedophilia, online games addiction and cyberbully. Pre and post surveys have been conducted during each training session. The results show that cybersecurity awareness training is one of the significant waysto increase knowledge regarding cybersecurity awareness starting at a young age. Hence, the finding supports that cybersecurity awareness must be encouraged among the young generation to develop a good digital citizen.